2023
DOI: 10.1111/sms.14427
|View full text |Cite
|
Sign up to set email alerts
|

Associations between combinations of 24‐h movement behaviors and physical fitness among Chinese adolescents: Sex and age disparities

Abstract: ObjectiveTo analyze the relationship between 24‐h movement behaviors and adolescents' physical fitness, with sex difference and age disparity explored specifically.MethodsA total of 135 852 Chinese adolescents aged 13–22 years were included in this cross‐sectional study. Self‐reported 24‐h movement behavioral times, including moderate to vigorous physical activity (MVPA), recreational screen, and sleep, were identified as meeting guidelines based on Canadian recommendations. Physical fitness indicator (PFI) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…A total of 61 studies ( 15 75 ) assessed adherence to 24-h movement guidelines ( Supplementary Table S4 ). Out of these, 44 ( 16 25 , 27 34 , 36 , 37 , 40 , 42 , 43 , 46 59 , 61 65 , 67 , 69 74 ) reported the proportions of participants meeting none of the guidelines, 30 studies ( 17 25 , 28 31 , 36 , 40 , 42 , 43 , 46 , 49 51 , 53 , 55 , 61 , 63 , 65 , 69 , 71 , 72 , 74 ) reported meeting only one guideline, 30 studies ( 17 22 , 24 , 25 , 28 31 , 36 , 40 , 42 , 43 , 45 , 46 , 49 51 , 53 , 55 , 61 , 63 , 65 , 69 , 71 , 72 , 74 ) reported meeting two guidelines, and 60 studies ( 16 75 ) reported meeting all three guidelines. For the specific combi...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 61 studies ( 15 75 ) assessed adherence to 24-h movement guidelines ( Supplementary Table S4 ). Out of these, 44 ( 16 25 , 27 34 , 36 , 37 , 40 , 42 , 43 , 46 59 , 61 65 , 67 , 69 74 ) reported the proportions of participants meeting none of the guidelines, 30 studies ( 17 25 , 28 31 , 36 , 40 , 42 , 43 , 46 , 49 51 , 53 , 55 , 61 , 63 , 65 , 69 , 71 , 72 , 74 ) reported meeting only one guideline, 30 studies ( 17 22 , 24 , 25 , 28 31 , 36 , 40 , 42 , 43 , 45 , 46 , 49 51 , 53 , 55 , 61 , 63 , 65 , 69 , 71 , 72 , 74 ) reported meeting two guidelines, and 60 studies ( 16 75 ) reported meeting all three guidelines. For the specific combi...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 39 studies ( 16 75 ) reported overall adherence to 24-h movement guidelines. Regarding age group, 26 studies ( 16 , 20 , 21 , 23 25 , 27 , 28 , 31 , 33 37 , 48 , 54 , 56 , 59 62 , 66 , 67 , 70 , 71 , 74 ) focused on children and 22 studies ( 20 , 22 , 26 , 28 , 30 32 , 38 , 46 , 48 , 52 , 53 , 56 58 , 62 , 64 , 66 , 69 , 72 74 ) focused on adolescents. In terms of gender, 19 studies ( 15 , 20 , 29 , 30 , 32 , 33 , 36 , 37 , 41 , 42 , 45 , 47 , 51 , 53 , 55 , 62 , 63 , 65 , 75 ) included both boys and girls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, it can be concluded that slightly more than 4 h of physical activity per day, including some moderate‐to‐vigorous intensity activity too, is good goal for children to ensure that their normal growth and maturation as well as fitness develop well in youth. This is important for counteracting worrying global trends in physical (in)activity and fitness in young people 21,22 . It is not forbidden for adults either to try to accumulate as much as possible daily physical activity, in one way or another, to maintain or even increase physical fitness still in adulthood and aging.…”
mentioning
confidence: 99%
“…This is important for counteracting worrying global trends in physical (in)activity and fitness in young people. 21,22 It is not forbidden for adults either to try to accumulate as much as possible daily physical activity, in one way or another, to maintain or even increase physical fitness still in adulthood and aging.…”
mentioning
confidence: 99%